Optimalisasi Pemahaman Pemanasan dan Pendinginan untuk Mencegah Cedera pada Klub Olahraga - Nurhidayat, Nurhidayat; Jariono, Gatot; Warthadi, Anugrah Nur; Sistiasih, Vera Septi; Hernawan, Budi (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
One of the goals of PKM is to avoid injury to body parts when exercising, so it is very important to do warm-up and cool-down exercises. Although warm-up activities performed gradually make the body sweat and increase its temperature, it helps the heart and blood vessels because it increases blood flow to the brain. For this reason, there needs to be training focused on "Strategies to increase understanding of the importance of warming up and cooling down when doing physical activity at the Punggawan Mosque Youth Sports Club, Surakarta". This training was held at the di Masjid Sholihin Jl. Gajah Mada No.97, Punggawan, Banjarsari, Surakarta City, Central Java. As a result of their service, participants gain useful knowledge and understanding of how to carry out warm-up and cool-down activities when exercising. Then every time you exercise, proper warm-up and cool-down can improve performance, temperature, blood flow and heart rate before exercise are also good, and injuries occur less frequently. Basically, cooling and warming up is really necessary to prepare the heart and blood vessels. In addition, it can help reduce the risk of cramps, injuries and muscle soreness after exercise.